Frequency of Helicobacter pylori in perforated peptic ulcer cases in a tertiary rural hospital - Sathanantham, Dinesh Kumar; Dave, Prakash; Beena, P. M.; P. N., Sreeramulu (International Surgery Journal, 2019)
Background: Helicobacter pylori infections have proven to be associated with gastritis and peptic ulcer, adenocarcinoma, gastric lymphoma. But its association with peptic ulcer perforations has not been completely proved. This study is intended to find out the association and give clarity of the pathology. The objective of the study was to observe the presence or absence of H. pylori in perforated peptic ulcer disease by obtaining biopsy from ulcer margin for rapid urease test, giemsa staining as well as serological method (antibodies IgA and IgG) Methods: This is an observational non-blinded study carried out in all cases of perforated peptic ulcer reporting in surgical wards, Emergency Department of the medical college during 2016-2018. Biopsy was taken from the ulcer margin and the tissue was subjected to histo-pathological examination, rapid urease test and blood sample was sent for serological examination. Results: Of the 46 patients participated in our study, 41 (89.1%) happened to be male, 5 (10.9%) were female. Only 2.2% of the patients were positive for H. pylori and remaining 95.7% were negative for H. pylori. The difference in the age group and H. pylori infection was found to be not statistically significant (p>0.05). Conclusions: In our study, frequency of H. pylori in perforated peptic ulcer cases was found to be only 2.2% which proves that there may be other contributing factors in perforated peptic ulcer cases, which need to be further evaluated.